Simulation of High Power THz Emission from Laser Interaction with Tenuous Plasma and Gas Targets (Communications in Computational Physics, 2008)
With one- and two-dimensional particle-in-cell (PIC) codes, we simulate thegeneration of high power terahertz (THz) emission from the interaction of ultrashortintense lasers with tenuous plasma and gas targets. By driving high-amplitude electron plasma waves either with a laser wakefield or the beatwave of two laser pulses,powerful THz electromagnetic pulses can be produced by linear mode conversion ininhomogeneous plasma or by the transient current induced at the surfaces of a thinplasma layer of few plasma wavelengths. Even with incident lasers at moderate intensity such as 1017W/cm2, the produced emission can be at the level of tens of MWin power and capable of affording field strengths of a few MV/cm, suitable for thestudies of THz nonlinear physics. With field ionization included in the PIC codes, THzemission from laser interaction with tenuous gas targets is simulated. It is found thatthe transient transverse current formed during the ionization processes is responsiblefor the THz emission. With this mechanism, one may also obtain THz fields of MV/cmat lower laser intensity as compared with the schemes of plasma-wave excitation.